Multi-layered historicity of the present : approaches to social science history - Vauhkonen, Jussi, 1977-; Rainio-Niemi, Johanna; Haggrén, Heidi (Helsinki : University of Helsinki, 2013)
"This book celebrates Professor Pauli Kettunen on his sixtieth birthday. In Pauli Kettunen's scholarship as well as in this collection, history meets social sciences in a manner that render distinctions between the two unnecessary. This book challenges simplistic views to history as 'a background' or 'development', opening up sophisticated perspectives to many up-to-date debates on, for instance, nationalism and globalization or the Nordic welfare models."--Takakansi.
Juhlakirja Pauli Kettuselle.
Sisältää bibliografisia viitteitä.
Julkaistu myös verkkoaineistona.
jufo:0
Keywords: Kettunen, Pauli, -- 1953-; Kettunen, Pauli, -- 1953- -- juhlajulkaisut; Palmgren, Raoul; historiantutkijat; historiantutkimus; sosiaalihistoria; taloushistoria; yhteiskuntatieteet; sosiaalitieteet; työväenluokka; sosiaalipolitiikka; hyvinvointipolitiikka; yritykset; sairausvakuutus; eläkeikä; toimeentuloturva; historia; juhlajulkaisut; nationalismi; historiker (forskare); historieforskning; socialhistoria; ekonomisk historia; samhällsvetenskaper; socialvetenskaper; arbetarklassen; socialpolitik; välfärdspolitik; företag; sjukförsäkring; pensionsålder; utkomstskydd; historia; festskrifter; nationalism